Cervix-rectum temperature differential at the time of insemination is correlated with the potential for pregnancy in dairy cows - Fernando LÓPEZ-GATIUS; Irina GARCIA-ISPIERTO; Ronald H.F. HUNTER (The Society for Reproduction and Development, 2021)
This study sought to establish whether temperature gradients between the cervix, vagina, and rectum at and 7 days post-artificial insemination (AI) were associated with the incidence of pregnancy in lactating dairy cows (Experiment I; n = 90 ovulating cows) and to evaluate temperature gradient dynamics from the time of insemination to 7 days post-AI under heat stress conditions (Experiment II; n = 16 ovulating and 4 non-ovulating cows). In Experiment I, 39 cows (43.3%) became pregnant. The odds ratio for pregnancy was 2.5 for each one-tenth of a degree drop in cervical temperature with reference to the control rectal temperature at the time of AI (P = 0.01), whereas the same decrease in the cervix-rectum temperature differential 7 days post-AI resulted in an odds ratio of 0.44 (P = 0.02). In Experiment II, 5 of the ovulating cows (31.3%) became pregnant. The mean values of the vagina-rectum, vagina-cervix, and cervix-rectum temperature differentials at AI (day 0), 8 h, 24 h, and 7 days post-AI changed significantly from day 0 to day 7 (within-subject effect; P < 0.02) in ovulating cows but not in non-ovulating cows. Temperature differentials on days 0 and 7 were similar between ovulating cows and cows of Experiment I. Overall, our findings support the notion that a temperature differential between the caudal cervical canal and rectum at AI may be an indicator of the likelihood of pregnancy. Possible prospects of confirming estrus at the herd-level are also suggested.